The Impact of Digital Transformation on Public organizations Effectiveness: Challenges and Post-Pandemic Recovery Strategies - Somnah, Meanih (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This examine investigates the impact of virtual transformation on public administration effectiveness within government organizations. A mixed-strategies approach, which include quantitative analyses including descriptive records, paired-samples t-assessments, regression analyses, ANCOVA, and Pearson correlational analyses, become employed to research records from a stratified random sample of presidency entities. Findings indicate a tremendous development in management effectiveness post-implementation of virtual tasks, with sturdy high quality relationships located between virtual transformation variables (use of digital gear, virtual talents training, integration of virtual structures) and administration consequences. ANCOVA effects highlight the have an effect on of virtual transformation adulthood levels on administration effectiveness. Pearson correlational analyses screen robust fine correlations between digital literacy degrees, use of virtual tools, and management effectiveness .